PENERAPAN PRINSIP-PRINSIP MUAMALAH: STUDI KASUS PEDAGANG PASAR TRADISIONAL - Koni, Agus; Safarudin Sidki , Dikri; Hidayat, Dayat; Dyah Wahyuningsih, Hartati; Nur Mastuti, Dian (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to diagnose how muamalah principles are practiced by traditional market traders in Indonesia. This study uses a phenomenological method to explore the experiences and perceptions of traditional market traders regarding the application of muamalah principles. The research sample consisted of 20 purposely selected traditional market traders. The results show that traditional market traders have implemented muamalah principles in an integrated manner in their business activities. They have applied the principles of justice (qist), honesty (siddiq), and courage (sidq) in interacting with customers and business partners. In addition, traditional market traders have also applied the principle of virtue (ihsan) in providing good service to customers. This study also found that the application of muamalah principles by traditional market traders is influenced by factors such as religious and cultural background, trading experience, and belief in muamalah principles. The results of this study can be used as a reference for the government and social institutions in developing programs that support the implementation of muamalah principles in traditional markets.